Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1155/2018/8732412
|View full text |Cite
|
Sign up to set email alerts
|

Hygiene Quality and Consumer Safety of Traditional Short- and Long-Ripened Cheeses from Poland

Abstract: The aim of this study was the assessment of the microbiological quality of three types of traditional cheeses which are produced from raw and pasteurized cow’s milk. Two types of cheeses were of the short-ripened type, and one cheese was long-ripened. A microbial examination was conducted for the presence of Salmonella spp. and Listeria monocytogenes microorganisms and the count of aerobic, psychrotrophic, lactic acid bacteria, and coliform bacteria, as well as Escherichia coli, Enterobacteriaceae, Enterococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Coliform bacteria, such as members of the Enterobacteriaceae family, are considered fundamental indicators of the hygiene practices during the production processes [49]. Specifically, regarding the manufacture and ripening of cheese, it has been shown that enterobacteria are present [50] and slowly decrease during ripening [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coliform bacteria, such as members of the Enterobacteriaceae family, are considered fundamental indicators of the hygiene practices during the production processes [49]. Specifically, regarding the manufacture and ripening of cheese, it has been shown that enterobacteria are present [50] and slowly decrease during ripening [51].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, regarding the manufacture and ripening of cheese, it has been shown that enterobacteria are present [50] and slowly decrease during ripening [51]. Other authors also demonstrated high levels of coliform contamination (from under 1 to 7.89 log CFU/mL) in different types of cheese, produced using traditional methods from cow's, goat's, sheep's or mixed milk [3,4,49]. Similar results were verified in the present study, since the Enterobacteriaceae levels ranged from 9.09 × 10 4 to 1.24 × 10 8 CFU/g of cheese, from the first to the last day of ripening, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulase-positive staphylococci exceeded the 5-log safety threshold in fresh raw milk cheese samples, whereas they were suppressed in all pasteurized milk cheese samples [39]. Pyz-Łukasik et al [40] reported that the levels of coliform bacteria, E. coli, and coagulase-positive Staphylococcus in the traditional short and long-ripened cheeses made with raw and pasteurized cow's milk indicated insufficient hygiene procedures during the production and that the cheeses did not comply with the criteria for food safety and hygiene according to the legislation.…”
Section: Effect Of Heat Treatment Of Milk On the Microbiological Characteristics Of White Cheesementioning
confidence: 97%
“…The total bacterial count (TBC) is the second important parameter of milk hygiene. The number and types of microorganisms in milk immediately after milking are affected by milking hygiene (cleanliness of milking equipment and access to water) [70][71][72][73]. Total bacterial count is a good indicator for monitoring sanitary conditions during the production and handling of dairy products.…”
Section: Microbiological Qualitymentioning
confidence: 99%